Witnessing (Dis)engagement: a Framework for Examining Legitimacy in the Criminal Courts - Kirby, Amy (The British journal of criminology, 2024)
This paper examines legitimacy in the criminal courts from the perspective of witnesses, an under-researched setting and participant group. Based on interviews with witnesses and observations of court proceedings, the paper provides a framework for examining how witnesses engage with the courts, arguing that ‘engagement’ can be used as a lens through which to understand legitimacy. The findings suggest that witnesses often display weak levels of engagement with the court process, which is indicative of strain in the ongoing legitimacy ‘dialogue’ (Bottoms and Tankebe 2012) between citizens and the state. The implications of this are explored.